PERKEMBANGAN DEPARTEMEN SUMBER DAYA MANUSIA SEBAGAI COST CENTER MENJADI PROFIT CENTER - Supraniningsih, Juliati (Lembaga Layanan Pendidikan Tinggi Wilayah III Jakarta, 2013)
In the globalization era, the business processes evolves rapidly and human resources become a very valuable and largest asset for company. Human Capital Management has a strategic role for the organization. The objective of this wiring is to discuss how to make the Human Resource Department which regarded as a cost centre can be made as a profit centre. The methods used library research with the descriptive and explorative approaches. It can be concluded that (1) the implementation of Human Resources Cost Management Technology can reduce administrative costs, consulting cost and service charge, because Human Resources Department could manage the vendor better and improve employee performance. (2) By developing the performance of Human Resources Department, can make their own profit for the company to act as external corporate entity, through providing human resource outsourcing services to the company itself and other companies which is a profitable business. (3) Human Resources Department is no longer as a cost center, but can be a profit center.